The Lived Experience of Inheritance for Muslim Widows in Contemporary South Africa - Megannon, Vayda (Department of Political Studies, 2021)
This empirical research explores experiences of inheritance in Muslim families, drawing upon case law, archival research and in-depth interviews with 6 Muslim widows in Cape Town. I examine women's experience of and attitudes towards inheritance in middle class Muslim families around Cape Town. This research aims to document Muslim widow's experiences of inheritance, furthermore, explore their attitudes towards these practices among their wider family. In particular, I investigate the experience of inheritance for Muslim widows, and interpret how these experiences relate to the governing principles of equality and diversity in the South African Constitution. This research has found that fairness and reciprocity serve as guiding principles of inheritance practices in middle class Muslim families around Cape Town. This is evidenced by two prominent practices of inheritance identified in the data, namely gendered conditionalities of inheritance shares, secondly the practice of gifting while alive. These findings indicate that to a large extent, on the micro level, the experiences of inheritance practices for Muslim women are in fact aligned with the principles of equality and diversity in the Constitution. However, these patterns of inheritance do occur in a context of gendered family practices. It is therefore argued that the challenge arises from the informality of inheritance practices among middle class Muslim families in Cape Town, characteristically occurring in the private sphere. In instances where fairness and reciprocity are not given primacy as guiding principles of inheritance practices, women tend to experience downward social mobility. Weak legal protection for Muslim widows during instances of discriminatory inheritances practices is resultant of the lack of a transformative mandate in the public sphere. Embedded within social forces, Muslim women's agency is conceptualised as proactively and strategically shaping their lives and the lives of female family members. Bringing the findings into conversation with transformative justice, there has been a stratification of rights and the realisation thereof, therefore resulting weak legal protection for Muslim widows in instances of discriminatory inheritance practices. It is further noted that existing international discourse regarding family law reform on a state level is relatable in this instance as gender-sensitive reforms do not in fact erode the foundations of religion and family, but merely challenge the tenuous balance of power. This research contributes to the developing body of literature on Muslim family practices in South Africa and acts as a lens in which to understand links between wider family history, and established social and institutional systems; therefore, leading to an evaluation of the role of transformative justice in this instance.